2023
DOI: 10.1021/acs.chemrestox.3c00114
|View full text |Cite
|
Sign up to set email alerts
|

Face Mask as a Versatile Sampling Device for the Assessment of Personal Exposure to 54 Toxic Compounds in Environmental Tobacco Smoke

Abstract: Exposure to environmental tobacco smoke (ETS), which contains hundreds of toxic compounds, significantly increases the risk of developing many human diseases, including lung cancer. The most common method of assessing personal exposure to ETS-borne toxicants is by sampling sidestream smoke generated by a smoking machine through a sorbent tube or filter, followed by solvent extraction and instrumental analysis. However, the ETS sampled may not truly represent the ETS in the ambient environment, due to complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…A single study was identified that attempted to quantify the cancer risk associated with bystander exposure to emissions from HTPs and compare this to the cancer risk associated with ETS exposure [ 189 ]. The described methodology used polyurethane foam facemasks worn by non-smoking volunteers present in the vicinity of smokers to collect emissions released by their smoking activity.…”
Section: Reviewmentioning
confidence: 99%
“…A single study was identified that attempted to quantify the cancer risk associated with bystander exposure to emissions from HTPs and compare this to the cancer risk associated with ETS exposure [ 189 ]. The described methodology used polyurethane foam facemasks worn by non-smoking volunteers present in the vicinity of smokers to collect emissions released by their smoking activity.…”
Section: Reviewmentioning
confidence: 99%
“…Therefore, children’s exposure to nicotine from secondhand vapor is likely to be substantially lower than that from secondhand smoke, and exposure to other harmful substances is likely to be lower still given that e-cigarette aerosol contains far fewer toxicants and carcinogens than tobacco smoke (and those that are remain are present in lower concentrations) . This reduced exposure has been shown in artificial settings (eg, rooms with a smoking machine set up to either vape or smoke) and nonrepresentative samples, but to our knowledge no studies have examined exposure among children in natural settings using nationally representative samples of the population.…”
Section: Introductionmentioning
confidence: 99%